Analisis Perbedaan Kurikulum Merdeka dan Kurikulum 2013 Ditinjau dari Aspek Sosial Budaya - Nurisra, Hafara; Anggeli, Nur Ifni Hayatib,; Anggeli, Anggeli; Mukhlis, Muhammad (UIR Press, 2025)
The 2013 Curriculum is known to be more structured and oriented toward national standards, thus limiting teachers’ creativity in connecting learning with local social and cultural contexts. In contrast, the Merdeka Curriculum offers greater flexibility for schools and teachers to adapt learning to the needs of students and the characteristics of local culture. This study aims to analyze in depth the differences between the Merdeka Curriculum and the 2013 Curriculum in terms of social and cultural aspects at various educational levels. The method used is literature study and analysis of curriculum documents as well as previous research findings. The results show that the Merdeka Curriculum places greater emphasis on project-based learning, integration of local culture in every activity, and authentic assessment that evaluates both the process and outcomes as a whole. The Merdeka Curriculum is also considered effective in building character, social skills, and appreciation for local culture, while the 2013 Curriculum tends to place social and cultural aspects only in local content and formal activities. Thus, this study provides an overview of the strengths and weaknesses of both curricula and offers recommendations for more effective implementation of social and cultural learning in schools.